Ascending aortic aneurysm exposed to direct impingement of eccentric flow jets through a tilting-disc valve prosthesis. Issue 5 (9th May 2019) - Nagamine, Hiroshi; Date, Yusuke; Takagi, Takeshi; Kawase, Yushi
Abstract: Single-leaflet tilting-disc aortic valve prostheses are known to generate eccentric transvalvular flow jets. These prostheses are routinely inserted with the major valve opening directed toward the non-coronary sinus to achieve more favorable hemodynamic performance. From the viewpoint of blood flow dynamics, the structural and functional properties of tilting-disc aortic valves resemble those of congenital bicuspid aortic valves with right- and left-coronary leaflet fusion, which have been associated with aortopathy in the ascending aorta. Here we describe the case of a patient who had undergone aortic valve replacement in 1987 with a Björk-Shiley tilting-disc valve and required reoperation for ascending aortic aneurysm 29 years later. Eccentric flow jets through the tilting-disc valve directly impinged on the posterior wall of the ascending aorta including the aortotomy suture line, possibly contributing to the development of the saccular aneurysm in the ascending aorta.